Perencanaan Pajak sebagai Upaya Penghematan Pajak - Siti Rochmah Ika (Jurnal Akuntansi dan Bisnis, 2004)
Tax planning is an effort to minimize the tax liability. To achieve the objective of the Tax planning, tax complience and bookkeeping are required. Several strategies could be done to minimize the tax liability in several ways, such as choosing the business forms, choosing the area of business, consider the profit allocation in the end of year, delay to receive the income, and utilize discount.